The correlation between writing attitude and academic writing competence at state university in Bengkulu city - Julmukya, Tiarsa; Sujarwati, Iis; Sofyan, Dedi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to examine the correlation between students’ writing attitudes and academic writing competence among state university students in Bengkulu City. The samples of this research were 111 University students. This research used three instruments, they are: questionnaire, writing test, and interview. This research used a mixed-method design with the explanatory sequential design. The data were analyzed by using application SPSS 29. The mean result of writing attitude was 74.31. It was categorized as had positive attitude. The mean result of academic writing competence was 78.87. It was categorized as very good. Pearson product moment correlation was used to find out the correlation between. writing attitude and writing competence. The result showed that Pearson correlation coefficient (r) is 0.824, indicating a very strong positive correlation between writing attitude and academic writing competence. Based on the interview the affective responses revealed that students generally perceived academic writing as a vital component of their academic development. Most participants acknowledged that writing facilitates the communication of ideas, enhances critical thinking, and supports the demands of academic and professional tasks.